A Survey About Forced Intercourse in Marriage - Yavuz, Mehmet Fatih; Gölge, Zeynep Belma; Safran, Nurhas (The Bulletin of Legal Medicine, 1998)
The purpose of this study was to determine the opinions of the jurists and society about marital rape. The questionnaires were completed by 170 jurists and 480 from the society. 48 % of the jurists, 71 % of the ones from the society and 65 % in general, agree that the forced sexual intercourse in the marriage is a rape crime. As more than the half of the participants have agreement, marital rape should be seriously discussed to be reserved in Turkish laws as a rape crime. Key words: Marital rape.